2012
DOI: 10.1007/s00425-012-1722-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tomato (Solanum lycopersicum L.) root growth by cyanamide is due to altered cell division, phytohormone balance and expansin gene expression

Abstract: Cyanamide (CA) has been reported as a natural compound produced by hairy vetch (Vicia villosa Roth.) and it was shown also to be an allelochemical, responsible for strong allelopathic potential in this species. CA phytotoxicity has been demonstrated on various plant species, but to date little is known about its mode of action at cellular level. Treatment of tomato (Solanum lycopersicum L.) roots with CA (1.2 mM) resulted in inhibition of growth accompanied by alterations in cell division, and imbalance of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
59
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 41 publications
12
59
0
4
Order By: Relevance
“…The development of analytical techniques allowing better specification of direct effects of allelopathins, have moved the exploration (or the research on) of this phenomenon from fields into laboratories. The term "allelopathy" refers rather to interactions occurring in the natural environment [5]. For studies with plant extracts, allelopathins isolated from plant tissue, collected from exudates or even synthetic compounds identical to natural ones, it was established the term ''phytotoxicity'' to distinguish allelopathy (as a phenomenon occurring in natural environment) from studies conducted in laboratory.…”
Section: Allelopathic Interactions and Allelopathic Compoundsmentioning
confidence: 99%
“…The development of analytical techniques allowing better specification of direct effects of allelopathins, have moved the exploration (or the research on) of this phenomenon from fields into laboratories. The term "allelopathy" refers rather to interactions occurring in the natural environment [5]. For studies with plant extracts, allelopathins isolated from plant tissue, collected from exudates or even synthetic compounds identical to natural ones, it was established the term ''phytotoxicity'' to distinguish allelopathy (as a phenomenon occurring in natural environment) from studies conducted in laboratory.…”
Section: Allelopathic Interactions and Allelopathic Compoundsmentioning
confidence: 99%
“…Cyanamide solution, in a petri-dish assay, decreased the quantity of mitotic cells, suppressed the propagation of meristematic cells, and altered the cytoskeleton arrangement in onion (Allium cepa L.) [34]. In a subsequent study on tomato, cyanamide inhibited root growth, likely due to altered cell division, an imbalance of the hormones ethylene and auxin, and differences in expansin gene expression [35]. To date, no research has been conducted on cyanamide mode of action using the species evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Bleach blue color as well as its lower incidence indicating decreased O 2 · -content after 3 days of CA treatment may be an effect of inhibition of cell proliferation and root tip shrinkage. 5 On the other hand, decreased H 2 O 2 may be related to disorder in differentiation of cells that have already moved from the meristematic zone.…”
Section: Ca As a Plant Growth Inhibitormentioning
confidence: 99%
“…4 Our former studies, conducted on tomato seedlings, indicated disturbances in root tip cells division leading to reduction of length of root tip zone, as the main reason of CA-induced root growth inhibition. 5 This, in consequence, reorganized every other root zones. Moreover, disorder in mitosis was correlated with altered expression of expansin genes (LeEXPA9 and LeEXPA18) involved in reconstitution of cell wall after Mode of action of allelochemicals in target plants is currently widely studied.…”
mentioning
confidence: 95%
See 1 more Smart Citation